Cultures and entrepreneurial competencies; ethnic propensities and performance in Malaysia - Tehseen, Shehnaz *; Anderson, Alistair (Emerald, 2020)
Purpose-The purpose of this study is to examine the extent and types of entrepreneurial competences among culturally different ethnic groups in Malaysia. Malaysia offers us a similar environment and ecosystem to make comparisons within a single context. Design/methodology/approach-This paper surveyed 600 respondents – 200 Malaysian Chinese, 200 Malaysian Indians and 200 Malays – and collected data about the types of competencies and about self-reported growth as firm performance. The study used PLS-SEM for inferential testing and PLS-MGA to conduct multigroup analysis among the three ethnic groups and found considerable and interesting differences. Findings-The results of the nuanced, fine-grained findings showed a distinctive distribution of competencies. This study investigates the analysis further to argue that there is an ethnic disposition to favour and value different competencies. Broadly, Malaysian Chinese have a commercial outlook which contrasts with the Malaysian emphasis on social values such as family. Malaysian Indians’ competencies are similar to Malaysian Chinese’s, but with more social value emphasised. This distribution impacts on firm performance with Malaysian Chinese firms faring economically better. However, this economic measure takes no account of social measures which may be an important determinant and motivation for some ethnic groups. Research limitations/implications-Theoretically, it becomes evident that one size does not fit all. In practice, different competencies are prioritised. Hence competencies appear to be culturally shaped. Culture influences what might be seen as very practical dimensions of entrepreneuring. From a practical perspective, those encouraging entrepreneurship should take such differences into account. Originality/value-The study is original in comparing cultural effects on competencies and performance